The benefits of multiple recollection strategies on adolescents' testimonies: quality versus within-statement consistency?. Issue 2 (9th May 2016) - van Can, Sanne; Dodier, Olivier; Otgaar, Henry; Verkampt, Fanny
Abstract : Purpose: – The purpose of this paper is to examine the beneficial effect of a modified cognitive interview (MCI) on adolescents' testimonies in case of a negative emotional event. Furthermore, the authors were interested in assessing the impact of a MCI on within-statement consistency. Design/methodology/approach: – In total, 37 adolescents (12-15 years) watched a emotionally negative video and were interviewed, seven days later, with a MCI or a structured (control) interview (SI). Findings: – Results showed that adolescents interviewed with the MCI reported significantly more correct and tended to report more incorrect information than those interviewed with the SI. Nonetheless, this rise in incorrect details did not impair the accuracy of statements gathered with the MCI (vs SI). Moreover, consistent, reminiscent, and forgotten information within a statement was positively linked to overall accuracy. In conclusion, testimonies gathered with the MCI might be perceived as more complete and detailed than the ones gathered with the SI. Practical implications: – The improvement of interview techniques helps solving criminal cases. Originality/value: – The innovative aspect of this work is that the benefits of the cognitive interview (CI) and the absence of an effect of inconsistency on accuracy are now also seen among adolescents.